Revitalisasi Prinsip Pendidikan Hieronimus bagi Pendidikan Perempuan di Indonesia: Kajian Historis dan Kontekstual - Cahyono, Heru; Hasiholan, Anggi Maringan (STT Iman Jakarta, 2025)
The revitalization of women's education requires an approach that emphasizes not only cognitive development but also spirituality, ethics, and social engagement. The principle of Disciplina Christiana, derived from Jerome's ascetic thought, provides an alternative curricular framework for addressing the challenges of women's education in Indonesia's plural and patriarchal context. The focus lies in shaping women as autonomous subjects—faithful, critical, and compassionate—rather than passive objects within the educational system. This study aims to formulate a transformative educational model by employing a qualitative method with a historical-hermeneutical approach and theological analysis. Three key areas are highlighted: lectio sacra as a spiritual practice that helps women connect with their faith, disciplina vitae to develop strong morals and self-discipline, and actio caritatis as a way to engage in helping others and promoting social justice actively. These pillars are integrated into the contextual and transformative praxis of Christian religious education. The result is a curricular model that not only shapes character but also strengthens women's agency and participation in building a more just and compassionate society. Abstrak Revitalisasi pendidikan perempuan membutuhkan pendekatan yang tidak hanya menekankan aspek kognitif, tetapi juga spiritualitas, etika, dan keberpihakan sosial. Prinsip Disciplina Christiana dari pemikiran asketik Hieronimus memberikan ide untuk kurikulum alternatif yang cocok untuk mengatasi tantangan pendidikan perempuan di Indonesia yang beragam dan patriarkal. Fokusnya adalah pada pembentukan perempuan sebagai subjek otonom yang beriman, kritis, dan berbelarasa, bukan sebagai objek pasif dalam sistem pendidikan. Penelitian ini bertujuan untuk merumuskan model pendidikan yang transformatif dengan menggunakan metode kualitatif dan pendekatan hermeneutik historis serta analisis teologis. Tiga pilar utama yang dikembangkan adalah lectio sacra sebagai praktik spiritual yang membantu perempuan mengenali identitas religius, disciplina vitae sebagai cara untuk membangun ketahanan moral dan keteraturan hidup, serta actio caritatis sebagai motivasi untuk terlibat aktif dalam pelayanan dan keadilan sosial. Ketiga pilar ini diintegrasikan ke dalam praksis Pendidikan Agama Kris-ten yang kontekstual dan transformatif. Hasilnya adalah model kurikulum yang tidak hanya membentuk karakter, tetapi juga memperkuat agensi dan partisipasi perempuan dalam masyarakat yang lebih adil dan penuh kasih.